2018
DOI: 10.3389/fpls.2018.01549
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 Signature and Innate Antioxidative Profile Make the Difference Between Sensitivity and Tolerance to Salt in Rice Cells

Abstract: Salt tolerance is a complex trait that varies between and within species. H2O2 profiles as well as antioxidative systems have been investigated in the cultured cells of rice obtained from Italian rice varieties with different salt tolerance. Salt stress highlighted differences in extracellular and intracellular H2O2 profiles in the two cell cultures. The tolerant variety had innate reactive oxygen species (ROS) scavenging systems that enabled ROS, in particular H2O2, to act as a signal molecule rather than a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…In particular, most of genes involved in photosynthesis, such as those encoding chlorophylls and photosystems subunits, were down-regulated ( Figure 2 B), indicating the programed dismantling of photosynthetic apparatus. This result was in line with our previous findings that VN plants (and cultured cells) under salt stress initiated a programmed cell death (PCD) response and leaf senescence [ 47 , 48 ]. On the contrary, tolerant Baldo plants regulated few genes that were grouped into stress response, transport, hormones, transcription, and protein catabolism categories ( Figure 2 A,C).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In particular, most of genes involved in photosynthesis, such as those encoding chlorophylls and photosystems subunits, were down-regulated ( Figure 2 B), indicating the programed dismantling of photosynthetic apparatus. This result was in line with our previous findings that VN plants (and cultured cells) under salt stress initiated a programmed cell death (PCD) response and leaf senescence [ 47 , 48 ]. On the contrary, tolerant Baldo plants regulated few genes that were grouped into stress response, transport, hormones, transcription, and protein catabolism categories ( Figure 2 A,C).…”
Section: Resultssupporting
confidence: 92%
“…In previous works, we explored the salt tolerance/sensitivity of two Italian rice varieties of great economic relevance for both the internal (Vialone Nano, VN, salt sensitive) and external (Baldo, salt tolerant) Italian markets [ 47 , 48 ]. We demonstrated that prompt H 2 O 2 signaling at root level was of most importance in inducing salt tolerance in the Baldo variety and that a delay in response led the sensitive variety VN to a chaotic response and leaf senescence ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference can be ascribed to a delay of the response of the salt-susceptible genotype. Consistently, Formentin and colleagues [46,47] demonstrated that the salt-tolerant genotype is able to activate a faster stress response as compared to the salt-susceptible genotype, through an early activation of H 2 O 2 and hormone signalling pathways.…”
Section: Resultsmentioning
confidence: 70%
“…GSH feeding of Arabidopsis seedlings appears to induce the expression of stress-related genes and down-regulates developmental correlated genes (Hacham et al, 2014). High GSH levels have also often been correlated to increased stress tolerance (Cao et al, 2017; Ferrer et al, 2018; Formentin et al, 2018). Conversely, GSH deficiency in Arabidopsis root meristem less 1 mutant ( rml1 ) has been shown to affect root growth and architecture through a massive transcriptome re-programming.…”
Section: Role Of Redox Balance In Transcriptional Controlmentioning
confidence: 99%